Chemical constituents of Clathria reinwardti. (25th October 2022) - Trang, Do Thi; Hang, Dan Thi Thuy; Dung, Duong Thi; Bang, Ngo Anh; Huong, Phan Thi Thanh; Yen, Pham Hai; Tai, Bui Huu; Cuc, Nguyen Thi; An, Do Hoai; Nhiem, Nguyen Xuan; Thung, Do Cong; Van Kiem, Phan
Abstract: Seven compounds, dihydrosinularin (1 ), 11 ‐epi‐ sinulariolide acetate (2 ), 10, 18‐diacetoxydilabella‐2, 7‐dien‐6‐one (3 ), 4‐(2′, 3′, 4′‐trimethylphenyl)‐but‐(3 E )‐en‐2‐one (4 ), 4‐hydroxybenzaldehyde (5 ), indole‐3‐aldehyde (6 ), and methyl indole‐3‐carboxylate (7 ) were isolated from Clathria reinwardti . The isolates were identified by ESIMS, 1D and 2D NMR spectra. Compounds 1‐4 significantly exhibited the cytotoxic activity against SK‐LU‐1, MCF‐7, HepG2, and SK‐Mel‐2 cell lines with the IC50 values ranging from 3.8 ± 0.1 to 23.0 ± 0.2 μM, compared to the positive control compound (ellipticine, IC50, ranging from 1.4 ± 0.2 to 1.7 ± 0.1 μM). This is the first report of these compounds from C. reinwardti . Abstract :